2001
DOI: 10.1038/sj.bmt.1702746
|View full text |Cite
|
Sign up to set email alerts
|

Atypical chronic graft-versus-host disease following interferon therapy for chronic myeloid leukaemia relapsing after allogeneic BMT

Abstract: Summary:We report a 54-year-old woman who received interferon alpha for haematological relapse of Ph-positive CML, 7 years after allogeneic BMT from an HLA-identical brother. Eighteen months after relapse, cytogenetic and molecular remission was achieved. She received interferon therapy for 25 months and it was discontinued when she developed skin lesions on her face and trunk, dysphagia and fever with respiratory failure and bilateral patchy airspace consolidation of the lung without microbiologic findings. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Considering that the patient remains in molecular remission 6 months after cessation of interferon-␣ during which time chronic GVHD has persisted, chronic GVHD, probably induced by interferon-␣, might have contributed to the durable remission in this patient. Serrano et al recently reported a similar case, in which a patient developed atypical chronic GVHD following interferon-␣ for CML relapsing after allogeneic BMT [12] and in which the authors discussed the possible role of interferon in the pathogenesis of GVHD. The patient developed skin lesions on her face and trunk, dysphagia, and fever with respiratory failure and bilateral patchy airspace consolidation of both lungs.…”
Section: Discussionmentioning
confidence: 94%
“…Considering that the patient remains in molecular remission 6 months after cessation of interferon-␣ during which time chronic GVHD has persisted, chronic GVHD, probably induced by interferon-␣, might have contributed to the durable remission in this patient. Serrano et al recently reported a similar case, in which a patient developed atypical chronic GVHD following interferon-␣ for CML relapsing after allogeneic BMT [12] and in which the authors discussed the possible role of interferon in the pathogenesis of GVHD. The patient developed skin lesions on her face and trunk, dysphagia, and fever with respiratory failure and bilateral patchy airspace consolidation of both lungs.…”
Section: Discussionmentioning
confidence: 94%
“…IFNα treatment exacerbates disease in lupus-prone murine models (54, 55), and produces lupus-like rashes and anti-nuclear antibodies in man (56). Similarly, use of IFNα after transplant to treat patients relapsing with chronic myelogenous leukemia has been reported to produce severe CGVHD (57, 58). The commonalities between CGVHD and systemic autoimmune disorders are particularly relevant to the development of new approaches to CGVHD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic role of IFN-a in graft-versus-host disease (GVHD) and graft-versus-leukemia (GVL) has been known for decades [70,71], especially in the context of relapsing chronic myeloid leukemia following bone marrow transplantation [72]. However, the mechanisms of action remain obscure, and the application of type I IFN in this setting remains controversial [73,74]. A study by Robb et al [75] suggested that the efficacy of type I IFN in protecting patients from GVHD and GVL can be attributed to the suppression of donor CD4 ?…”
Section: T Cellsmentioning
confidence: 99%